Semiochemical tracks of predaceous Coccinellidae (Coleoptera) modulate feeding attributes and assimilation of nutrients in Zygogramma bicolorata (Coleoptera: Chrysomelidae). Issue 3 (27th June 2020) - Patel, Priya; Kumar, Bhupendra; Upadhyay, Rekha; Bhusal, Daya Ram; Kumar, Dinesh
Abstract: Parthenium hysterophorus Linnaeus (Asteraceae) is a toxic weed found abundantly in major agroecosystems of the world. The weed is inhabited by both phytophagous Chrysomelidae (Coleoptera), used as biocontrol agents, and the predaceous Coccinellidae (Coleoptera). The present investigation was designed to assess the feeding attributes and larval development of Zygogramma bicolorata Pallister (Coleoptera: Chrysomelidae) in the presence of semiochemical tracks of coccinellid beetles. Results revealed that the presence of coccinellid semiochemical tracks on the weed reduced larval consumption rates, conversion efficiencies, and growth rates. The feeding deterrent effects of the semiochemical tracks were species specific. Larvae accumulated lower concentrations of glucose, proteins, and triacylglycerols and exhibited reduced body biomass in the presence of semiochemical tracks. The coccinellid semiochemical tracks also promoted Z. bicolorata larvae to accelerate their developmental rates and develop faster than the larvae reared in the absence of semiochemical tracks. While the fourth instars consumed food maximally and were heavier, their food use efficiencies were lower than the other instars. Our findings, therefore, suggest that the presence of semiochemical tracks of coccinellids on P. hysterophorus impedes its biological control by Z. bicolorata larvae.